Irony and sarcasm - Kreuz, Roger J. 1961- (The MIT Press, 2020)
"This book provides a concise summary of the concepts "irony" and "sarcasm": what they mean, how they have been used over time, and how they differ from the related concepts like coincidence, paradox, satire, and parody. The use of these terms, from Greek philosophers to postmodern theorists, is briefly sketched, and empirical research on why people use such language, and how it is comprehended, is provided. The book is leavened with quotations about irony and sarcasm, examples from popular culture (including an analysis of Alanis Morissette's song "Ironic"), television programs, and the use of irony and sarcasm online, both in words and also via emoticons, emoji, hashtags, and internet memes. The book is unique in that it provides a succinct yet comprehensive overview of the history of these terms, as well as empirical research by cognitive scientists. It will provide careful writers with the background and context that is necessary to employ these terms with confidence, or to use other terms if they are more appropriate"--
Keywords: Irony; Semantics; Ironie; Sarkasmus